The virtues in psychiatric treatment - Peteet, John Raymond (Frontiers in Psychiatry, 2023)
Virtues, understood as excellent character traits, originally defined human flourishing, but have been historically neglected within psychiatric practice. Reasons include concerns about scientific objectivity, realistic expectations, and therapeutic moralism. Renewed interest in their clinical relevance has been spurred by problems in sustaining professionalism, growing attention to virtue ethics, empirical support for the benefits of virtues such as gratitude, and the emergence of a fourth wave of growth promoting therapies. Increasing evidence supports the incorporation of a virtues based perspective into diagnostic assessment, goal-setting, and treatment.